2015
DOI: 10.2147/clep.s72906
|View full text |Cite
|
Sign up to set email alerts
|

Adverse pregnancy outcomes after exposure to methylphenidate or atomoxetine during pregnancy

Abstract: ObjectiveTo determine if prenatal exposure to methylphenidate (MPH) or atomoxetine (ATX) increases the risk of adverse pregnancy outcomes in women with attention deficit/hyperactivity disorder (ADHD).Materials and methodsThis was a population-based cohort study of all pregnancies in Denmark from 1997 to 2008. Information on use of ADHD medication, ADHD diagnosis, and pregnancy outcomes was obtained from nationwide registers.ResultsWe identified 989,932 pregnancies, in which 186 (0.02%) women used MPH/ATX and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 25 publications
4
45
1
Order By: Relevance
“…24 A recent cohort study compared women who used ADHD medication and women with ADHD diagnosis without medication to women with no ADHD diagnosis or medication in the general population of pregnancies in Denmark from 1997–2008. 25 They reported that methylphenidate or atomoxetine use in pregnancy (n=186) was not associated with reduced birthweight or gestational age at birth. However, they reported that women with a hospital-based diagnosis of ADHD who did not use medication (n=275) were at an approximately 2-fold increased risk of preterm birth.…”
Section: Discussionmentioning
confidence: 98%
“…24 A recent cohort study compared women who used ADHD medication and women with ADHD diagnosis without medication to women with no ADHD diagnosis or medication in the general population of pregnancies in Denmark from 1997–2008. 25 They reported that methylphenidate or atomoxetine use in pregnancy (n=186) was not associated with reduced birthweight or gestational age at birth. However, they reported that women with a hospital-based diagnosis of ADHD who did not use medication (n=275) were at an approximately 2-fold increased risk of preterm birth.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, eight cohort studies were eligible for inclusion in this review. We included three studies that used the Danish National Patient Registry because they reported different maternal and neonatal outcomes, although there was some overlap in the study periods.…”
Section: Resultsmentioning
confidence: 99%
“…150 The 2014 systematic review did not include the results of three population based Danish cohort studies (n=186 methylphenidate or atomoxetine; n=480 methylphenidate, modafinil, and atomoxetine; n=222 methylphenidate alone). [151][152][153] The first study found that prenatal exposure was associated with an increased risk of spontaneous abortion (adjusted relative risk 1.55, 1.03 to 2.36) and lower Apgar scores (2.06, 1.11 to 3.82). 151 The second found that prenatal exposure was associated with increased risk of elective terminations of pregnancy by maternal request (odds ratio 4.70, 3.77 to 5.85) and by special indication (2.99, 1.34 to 6.67) and of miscarriage (2.07, 1.03 to 2.36).…”
Section: Resultsmentioning
confidence: 99%
“…[151][152][153] The first study found that prenatal exposure was associated with an increased risk of spontaneous abortion (adjusted relative risk 1.55, 1.03 to 2.36) and lower Apgar scores (2.06, 1.11 to 3.82). 151 The second found that prenatal exposure was associated with increased risk of elective terminations of pregnancy by maternal request (odds ratio 4.70, 3.77 to 5.85) and by special indication (2.99, 1.34 to 6.67) and of miscarriage (2.07, 1.03 to 2.36). 152 However, the women using stimulants were more likely to be young, single, less well educated, receiving social security, and taking other psychotropics.…”
Section: Resultsmentioning
confidence: 99%